Optimal Formation Portfolio: An Analysis Using the Markowitz and Single Index Model for IDX30 Stock Period (2016-2021) (The Indonesian Journal of Business Administration, 2022)
This research paper aims to evaluate the performance of the stocks listed in the IDX30 throughout five years (2016-2021). The evaluation of the IDX30 stocks is done by analysing the value of each stock through its risk and return to then bring forth an optimum portfolio. In order to come up with an optimum portfolio, the evaluation of the 17 stocks can be calculated through two methods which are the Markowitz Model and the Single Index Model. The findings of this research show that the Markowitz model produces 16 portfolio simulations with one optimum portfolio: Portfolio 2 with a return of 17.68% annually, and a standard deviation of 18.65%. The Single Index Method produces a portfolio with a return of 33.6% annually. Through this research, it can be deduced that as the Single Index Method evaluates more stocks, it also conveys better overall performance than the stocks evaluated by the Markowitz Model. However, the findings also convey that the calculation of the return presented by both Markowitz and Single Index methods is higher than JCI, hence showing that stock performance is more secure and less penetrable within the risk-free market.Keywords: investment, portfolio, return, risk, Markowitz, Single Index